The Temperature Effect on the Physical Properties of CoMnSb Half-Heusler Ferromagnetic: Density Functional Theory and Monte Carlo Simulation. (1st March 2022) - Azouaoui, A.; Hourmatallah, A.; Benzakour, N.; Bouslykhane, K.
Abstract : In this work, we have studied the effect of temperature on structural, magnetic, electronic, elastic, thermodynamical properties of half-Heusler CoMnSb by using density functional theory (DFT) and Monte Carlo simulations. The semi-classical Boltzmann transport theory in combination with DFT is implemented to evaluate the thermoelectric (TE) properties. The obtained ground state properties show that CoMnSb has a half metallic character with a magnetic moment value of about 3 μ B . Thermodynamical parameters have been studied using quasi-harmonic approximation (QHA) in the range of temperature 0–1000 K. The results of QHA show that the CoMnSb maintain their mechanical stability under temperature. The obtained results of TE properties show that CoMnSb exhibits a low lattice thermal conductivity and that ZT increases with temperature and reaches the maximum value of 0.098 at 1000K. The Monte Carlo simulation is used to investigate the magnetic properties of CoMnSb. Moreover, the transition temperature T C and the hysteresis cycle are calculated. These properties show that the CoMnSb half-Heusler is a good candidate for spintronic applications.